2008
DOI: 10.1007/s00534-007-1312-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anatomic resection vs nonanatomic resection for small nodular hepatocellular carcinoma based on gross classification

Abstract: In patients with HCC nodules equal to or less than 3 cm and with the nonboundary type, anatomic resection should be employed to the extent that liver function allows, because this procedure would be more favorable than nonanatomic resection in eradicating micrometastases that have extended away from the tumor's margin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 34 publications
3
91
1
1
Order By: Relevance
“…However, in a different study, anatomic resection achieved better recurrence-free survival rate in small HCC (≤3 cm) accompanied by three or fewer nodules (44). They also determined that success rate was more prominent in nonboundary type HCC (single nodular type with extranodular growth, confluent multinodular type, and invasive type) than in the boundary type (single nodular type) (44). They also revealed that the distance of micrometastases from the main mass was significantly longer in the nonboundary type (9.5 mm) than in the boundary type (3.1 mm) (44).…”
Section: The Effect Of Microvascular Invasion On Treatment Surgerymentioning
confidence: 87%
See 3 more Smart Citations
“…However, in a different study, anatomic resection achieved better recurrence-free survival rate in small HCC (≤3 cm) accompanied by three or fewer nodules (44). They also determined that success rate was more prominent in nonboundary type HCC (single nodular type with extranodular growth, confluent multinodular type, and invasive type) than in the boundary type (single nodular type) (44). They also revealed that the distance of micrometastases from the main mass was significantly longer in the nonboundary type (9.5 mm) than in the boundary type (3.1 mm) (44).…”
Section: The Effect Of Microvascular Invasion On Treatment Surgerymentioning
confidence: 87%
“…Nakashima et al (21) and Ueno et al (44) reported that the distance between the micrometastasis and the main tumor was 10 mm or shorter in most of the patients. Thus, it is crucial to ablate the main tumor with an adequate surrounding liver tissue of ≥10 mm to prevent the recurrence and local control of MVI (28, 48).…”
Section: Locoregional Treatmentmentioning
confidence: 95%
See 2 more Smart Citations
“…If the HCC is smaller in size, one could reasonably deduce that there would be no statistical difference in the DFS after AS or MH since the risk of dissemination is presumably negligible, which means that both techniques had efficacy equivalent to that of local ablative therapy. If the HCC is larger, most patients will already have macroscopic vascular invasion or satellite nodules that will result in a high incidence of recurrence (14). This means a more advanced stage of HCC and evidence of the oncological behavior of the HCC, potentially offsetting the effects of the technique used.…”
Section: Anatomical Vs Non-anatomical Resectionmentioning
confidence: 99%